Hubungan Antara Stres Kerja Dengan Kecelakaan Kerja Pada Pekerja Bagian Bekisting PT Kontsruksi X Di Kota Semarang - Muhammad Miftah Farid; Siswi Jayanti; Ekawati Ekawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Accident is undesirable events that can cause harm to individuals and companies. The highest accident rate in the current era is in the construction sector. Accidents are caused by several factors including management factors, basic causes and direct causes. The basic causes consist of personal factors and work factors. Personal factors that affect workplace accidents include physical, psychological, work stres and individual characteristics. Construction work has a high demand for work so that it becomes one of the factors arising from work stres symptoms in construction workers. This study aimed to analyze relationship between job stres and occupational accident on formwork construction worker Company X in Semarang City. This type of research is quantitative using cross-sectional study. The population in this study is 70 Formwork Construction Workers X in Semarang City. The sample used in the study using total sampling so that the respondent is a total of 70 respondents. The research instrument used was a questionnaire. The statistical analysis used is chi-square test. The results showed that there is a relationship between job stres with work accident with p-value (0.001). Researchers suggest that it could hold a joint exercise to make the worker's body becomes relaxed.